2019
DOI: 10.3390/machines8010001
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Manufacturing Strategy, Machining Conditions, and Finishing of a Radial Impeller

Abstract: Impellers are the most crucial components of pumps, as they directly determine the velocity profile of the fluid flowing through the pump and its efficiency. Given that the impellers have a complex geometry, they pose an important challenge to the manufacturer in order to construct them with the best possible dimensional accuracy and surface quality, and also achieve short machining times. In the present paper, the machining operations for the manufacture of a radial impeller were designed and implemented for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…Specimens were face milled using a CNC vertical machining center (ACE Micron) capable of working at a speed of 8000 rpm. The L16 orthogonal array (OA) design was chosen based on the Taguchi design of experiments [21] because the current study works with four input levels using four independent process parameters. Apart from reinforcement weight percentage, because of their importance in the face milling process, cutting speed, feed rate, and depth of cut have been used as input parameters.…”
Section: Experimental Setup and Designmentioning
confidence: 99%
“…Specimens were face milled using a CNC vertical machining center (ACE Micron) capable of working at a speed of 8000 rpm. The L16 orthogonal array (OA) design was chosen based on the Taguchi design of experiments [21] because the current study works with four input levels using four independent process parameters. Apart from reinforcement weight percentage, because of their importance in the face milling process, cutting speed, feed rate, and depth of cut have been used as input parameters.…”
Section: Experimental Setup and Designmentioning
confidence: 99%
“…Taguchi's approach introduces a design methodology for reduced labor costs with increased efficiency [47][48][49]. Its main purpose is quality engineering.…”
Section: Taguchi's S/n Ratio Methodsmentioning
confidence: 99%
“…Yet, the results demonstrated weak stability. Fotios et al [14] conducted an experimental investigation using Taguchi L 16 orthogonal array, selecting the best milling strategy and cutting conditions, as well as the appropriate tool to obtain the best process conditions so as to construct the impeller with the best dimensional accuracy and surface quality. The results showed that this optimization method improved the surface roughness of the impeller.…”
Section: Introductionmentioning
confidence: 99%